Implementasi Hukum Tata Ruang Dalam Pengelolaan Kampung Tongkol - Azimi Kahfi Putra Fananda; Muhamad Ikhwan Pratama; Agis Evaldo; Dzaki Indra Syabano (CV. ITTC INDONESIA, 2025)
This study examines the implementation of spatial planning law in the management of Kampung Tongkol, an example of an informal settlement attempting to adapt to spatial regulations in DKI Jakarta. Although legally the area is located in a high-density housing zone (R-8) based on the DKI Jakarta RTRW and RDTR, the actual conditions in the field show a mismatch between zoning provisions and the organically developing spatial use. Using a normative juridical research method with a legislative and conceptual approach, this study examines the legal framework, zoning status, and challenges of spatial planning implementation in vulnerable areas such as riverbanks. The results indicate that the main obstacles to zoning implementation include the lack of legal certainty of land ownership, high building densities exceeding the KDB and KLB provisions, vulnerability to flooding, and weak inter-institutional coordination. The Kampung Tongkol case also demonstrates the importance of a participatory approach and zoning review mechanisms so that spatial planning policies can adapt to the socio-economic realities of the community. These findings emphasize that the successful implementation of spatial planning law does not rely solely on normative regulations, but requires citizen involvement, policy flexibility, and the integration of environmental protection and spatial justice.